Supply Chain Management Model in Digital for Supervision Management in Cooperative Educationin the Universities - Artaphon Chansamut (International Journal of Supply Chain Management, 2023)
Supply chain management model in digital for supervision management in a cooperative education in the universities is composed of six elements namely main elements suppliers, manufacturer, Education customers, Consumers Satisfaction and Return. The objective of this research is to develop and to evaluate an appropriate about Supply chain management model in digital for supervision management in a cooperative education in the universities A sample consisted of ten experts in supply chain. Data analysis was the average mean and standard deviation. The results from ten experts agreement of about Supply chain management model in digital for supervision management in a cooperative education in the universities was a high level which means that model can develop digital for supervision management in a cooperative education.